IMPLEMENTASI STRATEGI DINAS KETAHANAN PANGAN DI KOTA PEKANBARU - Nukita Duana Nijou Siahaan; Abdul Sadad (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This study aims to determine the Implementation of the Strategy of the Food Security Service in Pekanbaru City by using the theory of the Implementation of wheelen and hunger strategies in (Setyo Ryanto, 2018), namely Programs, Budgets, and Procedures. This type of research is qualitative which is descriptive with data collection techniques are interviews, observations, and documentation. For the determination of the informant, the author used purposive sampling. Furthermore, to analyze the data obtained, the author used an interactive analysis model from Soegiyono. The results showed that the implementation of the Food Security Service Strategy in Pekanbaru City has not gone well, which can be seen from the three indicators that the authors used in this study. Factors that hinder the Implementation of the Food Security Service Strategy in Pekanbaru City are the lack of supervision carried out by the Pekanbaru City Food Security Service, the lack of evaluation carried out by the Pekanbaru City Food Security Service, and the lack of participation from the community. This has an impact on the Implementation of the Food Security Service Strategy in Pekanbaru City.